DAMPAK LATIHAN TUNGGAL HIGH INTENSITY INTERVAL TRAINING (HIIT) TERHADAP TEKANAN DARAH MAHASISWA PENDERITA HIPERTENSI PROGRAM STUDI ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI PADANG: THE IMPACT OF A SINGLE HIGH INTENSITY INTERVAL TRAINING (HIIT) SESSION ON BLOOD PRESSURE IN HYPERTENSIVE STUDENTS OF THE SPORT SCIENCE STUDY PROGRAM, UNIVERSITAS NEGERI PADANG - ego saputraa,; Alimuddin,; Muchlis , Arif Fadli; Ilham, (Jurnal IKEOR, 2026)
This study aims to determine the effect of a single High-Intensity Interval Training (HIIT) session on systolic and diastolic blood pressure levels among students in the Sports Science Program at Padang State University who were identified as having sedentary lifestyles and high blood pressure. The approach used in this study was quantitative with a quasi-experimental design employing an acute pretest-posttest design. The sample consisted of 25 students selected via purposive sampling based on their sedentary lifestyle and high blood pressure. The High-Intensity Interval Training (HIIT) intervention was conducted on a treadmill following the Modified Tabata Treadmill Protocol, consisting of 3 sets where the work phase was performed at an intensity of 65–75% HRmax with a speed of 7–9 km/h, while the active recovery phase took place at an intensity of 65–40% HRmax with a speed of 3–5 km/h. Blood pressure measurements were taken using an Omron digital sphygmomanometer at two time points: before the intervention and 40 minutes after the intervention was completed. The data analysis method applied in this study was the Paired Sample T-Test. The results showed that a single High-Intensity Interval Training (HIIT) session significantly reduced systolic (p < 0.05) and diastolic (p < 0.05) blood pressure. These findings indicate that a single High-Intensity Interval Training (HIIT) session is effective in lowering blood pressure in young adults with a sedentary lifestyle and hypertension, making it a viable non-pharmacological intervention for managing hypertension in the student population. Keywords: High Intensity Interval Training, blood pressure, hypertension, sedentary lifestyle, students